The Effect of Communication and Intrinsic Motivation on Employee Performance with Job Satisfaction as Mediation Variables - Ricky Aldian Ertanto; Prayekti Prayekti; Ignatius Soni Kurniawan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Employee performance is often interpreted as the level of achievement in carrying out an activity to realize the goals, objectives, and vision, and mission of the company through a strategic plan from the company. This study aims to determine the effect of communication and intrinsic motivation on employee performance with job satisfaction as a study mediation variable at the Yogyakarta Manpower and Transmigration Office. The population for this study was employees of the Yogyakarta Manpower and Transmigration Office. The sample used was 50 respondents. The technique used in this research is purposive sampling. This study uses a quantitative approach. The test instruments used in this study were validity and reliability tests. The data analysis technique used in this research is descriptive analysis, classical assumption test, normality test, multicollinearity test, heteroscedasticity test. Hypothesis testing used in this study is the t-test, path test, and Sobel test. The results showed that communication has a positive and significant effect on employee performance, Intrinsic Motivation has no positive and significant effect on employee performance, Job Satisfaction has a positive effect on performance, Communication has a positive effect on employee performance through Job Satisfaction, Job Satisfaction cannot mediate Intrinsic Motivation on Performance employees.